2008
DOI: 10.1016/j.jjcc.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of delayed enhancement magnetic resonance imaging for diagnosis and evaluation of cardiac function in patients with cardiac sarcoidosis

Abstract: DE-MRI is useful to diagnose the cardiac involvement of sarcoidosis and to evaluate cardiac function. It is likely that the distribution of DE in mid- to epi-myocardium is the characteristic of cardiac sarcoidosis, and the larger DE area may be correlated with poor LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…In accordance with other studies subepicardial LGE was almost exclusively found in patients with peri-/myocarditis [1,11] , while sarcoidosis another known disease with subepicardial enhancement and a cardiac involvement of 50% [20] did not show a specific pattern in our study [8,11] . However, as only 2 patients suffered from sarcoidosis in our study a detailed analysis of LGE pattern was not possible.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with other studies subepicardial LGE was almost exclusively found in patients with peri-/myocarditis [1,11] , while sarcoidosis another known disease with subepicardial enhancement and a cardiac involvement of 50% [20] did not show a specific pattern in our study [8,11] . However, as only 2 patients suffered from sarcoidosis in our study a detailed analysis of LGE pattern was not possible.…”
Section: Discussionsupporting
confidence: 93%
“…Late gadolinium enhancement (LGE) is a substantial part of CMR and is highly valued in both differentiating between ischemic and non-ischemic myocardial disease as shown by various studies [1][2][3][4][5][6][7][8][9][10][11] as well as identifying primary or secondary cardiomyopathy. LGE uses extracellular paramagnetic, Gadolinium-based contrast agents and reflects edema, myocyte necrosis or fibrosis of different etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, use of late gadolinium enhancement and T2-weighted MRI and 18F-fluorodeoxyglucose positron emission tomography for the detection of occult granuloma sites and residual sarcoidosis activity was reported. 18,19 Combined use of these multimodality techniques with gallium uptake may enhance prediction of corticosteroid effectiveness for VT recurrence. Late gadolinium enhancement MRI might have contributed to identification of patients requiring epicardial access.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Ohira et al have shown that cardiac MRI has a better specificity, but a lower sensitivity than FDG-PET [33]. The value of MRI in evaluation of the prognosis of the disease is directly dependent on the degree of myocardial involvement [6,34,35]. Since a powerful magnetic field may affect defibrillator settings, MRI is not safe for patients with pacemakers and implantable defibrillators and is not recommended in those cases [36].…”
Section: Discussionmentioning
confidence: 99%